Style and Architecture in a Democratic Perspective - de Bleeckere, Sylvain (Enquiry The ARCC Journal for Architectural Research, 2007)
The paper deals with research on structural relations between architectural education andcultural and human sciences. The paper addresses two major premises. Firstly the cultural role that architecture can play in the shaping of the ongoing process of democratisation of the global society. Derived here of is thesecond one: "What are the implications for our currentarchitectural education?” The argument develops over three stages.The first one concerns a subject in the field of cultural history, stating that, historically, architecture was commonly an expression of the ruling powers. The first paradigm is that of the earliest modern democracy, the USA. Its initial architectural expression was inspired by Thomas Jefferson who adapted the language of the classical order. The neoclassical style became the canon for the new state buildings: the capitols and the courthouses. This paradigm shows a contradiction and failure to project concepts of democracy and revolution into architecture. The second paradigm comes from the modern architectural movement of the interbellum period. It was inspired by revolutionary ideas of radical socialism and equal right movement, proclaimed and empowered by the USSR. This paradigm again shows ” albeit of another nature ” the failure to express the modern concept of democracy into an adequate architectural form. Both paradigms learn how astylistic canon dominated and misled the architectural shaping of a young, democratic society. In a second step, the paper focuses on two fundamental reflections. The first one highlights the relationship between democracy and style. A modern concept of liberty, for example, becomes visible in an architectural interpretation of Jefferson’s original design for the first Academic Village, Virginia. In the analysis of this architectural realisation, a more subtle image of Thomas Jefferson emerges. He was the founder of the Declaration of Independence, the philosophical basis for the first modern, democratic state. The second reflection dwells on the only consistent democratic philosophy of the 20th century, that of John Dewey. His concept of creative democracy is relevant to educate the ’democratic consciousness’ of young architects. It is further assumed that thinking in such a’democratic way’ can help to release architecture from a dogmatic stylistic canon.The third and final step addresses the implications for architectural education. The challenge is the shaping of the student’s social and political consciousness via an analysis of historical buildings freed from an encyclopaedic and uncritical approach.